ANALYSIS of ENVIRONMENTAL CONDITIONS, LEVELS of CHROMIUM (Cr) AIR AND ALBUMIN URINE LEVELS of WORKERS in the METAL COATING HOME INDUSTRY in the DISTRICT of CANDI SIDOARJO - HernyOcvian, Brevy Nella (International Journal of Psychosocial Rehabilitation, 2020)
Background of the electroplating process involves several chemicals such as chromium. Chromium plating workers are at high risk of chromium exposure. Air is one of the environmental components that have an important position for human needs. Research objectives analyze the environmental conditions, levels of chromium (CR) air and albumin urine levels of workers in the home industry of metal plating in the district of Candi Sidoarjo. The research method is a descriptive observational study by designing a crosssectional build with a sample number of 12 workers. The rate of chromium in the air is taken using EPAM 500 and then analyzed by the laboratory with atomic Absorption spectrophotometry (SSA). Environmental conditions (temperature and humidity) using Thermhygrometer. The rate of Albumin in Urine uses the method of ImmunoturBidimetric assay. Analysis of descriptive data analysis using coefficient contingency to know the strong relationship between variables. Results study, the result of the cross-tabulation show that workers with chromium levels exceeding the normal value of most are at workers working in the working environment with a rate of chromium in the air amounted to 0.01 mg/m3. The most positive albumin levels are in the non-production part of the cross-tabulation results showing a very strong connection to the temperature and humidity variables with chromium levels in the air with a coefficient contingency value of 0.707. Workers in the home industry of metal plating as much as 25% or 3 out of 12 workers have a positive rate of albumin, this indicated has occurred damage to kidney function. As much as (17%) or 1 out of 6 workers with normal and positive urine rate for albumin and as much as (33%) or 2 of 6 workers with chromium levels of urine exceeds the normal and positive limits of urine albumin levels. The study concludes that workers who have the most positive levels of albumin exist in nonproduction parts. Temperature and humidity have a strong relationship with the rate of chromium in air. It needs exhaust fan as supporting ventilation so that the air exchange can be faster and give plants around the industry so that the temperature is cool. Monitoring with home industry owners, local governments on the